2017
DOI: 10.17235/reed.2017.4771/2016
|View full text |Cite
|
Sign up to set email alerts
|

Cholangitis after endoscopic retrograde cholangiopancreatography: a rare complication?

Abstract: Cholangitis does not often occur after endoscopic retrograde cholangiopancreatography (ERCP), but it can be a serious complication of this procedure (1). Its clinical features, management and outcome are poorly characterized in the literature (2). In a recent study in a low-volume center (200 procedures in 22 months) the reported rate of this complication was less than 5%, with a tendency to reduce with increased experience of the practicioner (3). From a total of 487 ERCP performed in two years in our center,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…Our study revealed post-ERCP cholangitis in 9 (4.5%) patients. This finding is close to the Peixoto et al (32) study in Brazil, which found that post-ERCP cholangitis occurred in (4.9%) of patients. The mortality rate of ERCP in the present study was (0.5%).…”
Section: Discussionsupporting
confidence: 91%
“…Our study revealed post-ERCP cholangitis in 9 (4.5%) patients. This finding is close to the Peixoto et al (32) study in Brazil, which found that post-ERCP cholangitis occurred in (4.9%) of patients. The mortality rate of ERCP in the present study was (0.5%).…”
Section: Discussionsupporting
confidence: 91%
“…However, imaging may not specify all cases where biliary drainage is required. Few authors advocate a more aggressive approach in patients with post-ERCP cholangitis (20). Our study shows that PTBD is useful in the management of patients with post-ERCP cholangitis.…”
Section: Discussionmentioning
confidence: 57%
“…Its clinical features, management, and the outcome are poorly characterized in the literature [12]. In a recent study, (200 procedures in 22 months) the reported rate of POI was less than 5%, with a tendency to reduce with increased experience of the practitioner [12]. In our study, from a total of 28,525 ERCP performed, only 300 inpatients were diagnosed with comorbid POI.…”
Section: Discussionmentioning
confidence: 66%
“…Although there is no absolute evidence for the effectiveness of routine antibiotic prophylaxis on the frequency of septic complication after ERCP, the rate of bacteremia seems to decrease significantly. After ERCP, there is often temporary abdominal discomfort, transient fever, and hyperamylasemia [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation